Genetic diversity analysis of Croton antisyphiliticus Mart. using AFLP molecular markers - Oliveira, T. G. [UNESP]; Pereira, A. M. S.; Coppede, J. S.; Franca, S. C.; Ming, L. C. [UNESP]; Bertoni, B. W. (Funpec-editora, 2016)
Croton antisyphiliticus Mart. is a medicinal plant native to Cerrado vegetation in Brazil, and it is popularly used to treat urogenital tract infections. The objective of the present study was to assess the genetic variability of natural C. antisyphiliticus populations using AFLP molecular markers. Accessions were collected in the states of Minas Gerais, Sao Paulo, and Goias. The genotyping of individuals was performed using a LI-COR (R) DNA Analyzer 4300. The variability within populations was found to be greater than the variability between them. The F-ST value was 0.3830, which indicated that the populations were highly structured. A higher percentage of polymorphic loci (92.16%) and greater genetic diversity were found in the population accessions from Pratinha-MG. Gene flow was considered restricted (N-m = 1.18), and there was no correlation between genetic and geographic distances. The populations of C. antisyphiliticus exhibited an island-model structure, which demonstrates the vulnerability of the species.
Keywords: Euphorbiaceae; Medicinal plant; Cerrado; Conservation; LI-COR